IL-38 blockade induces anti-tumor immunity by abrogating tumor-mediated suppression of early immune activation - John P. Dowling; Pavel A. Nikitin; Fang Shen; Halley Shukla; James P. Finn; Nirja Patel; Cezary Swider; Jamie L. Bingaman-Steele; Chris Nicolescu; Eden L Sikorski; Evan J. Greenawalt; Michael J. Morin; et al. (mAbs)
Immune checkpoint inhibitors that overcome T cell suppressive mechanisms in tumors have revolutionized the treatment of cancer but are only efficacious in a small subset of patients. Targeting suppressive mechanisms acting on innate immune cells could significantly improve the incidence of clinical response by facilitating a multi-lineage response against the tumor involving both adaptive and innate immune systems. Here, we show that intra-tumoral interleukin (IL)-38 expression is a feature of a large frequency of head and neck, lung and cervical squamous cancers and correlates with reduced immune cell numbers. We generated IMM20324, an antibody that binds human and mouse IL-38 proteins and inhibits the binding of IL-38 to its putative receptors, interleukin 1 receptor accessory protein-like 1 (IL1RAPL) and IL-36R. In vivo, IMM20324 demonstrated a good safety profile, delayed tumor growth in a subset of mice in an EMT6 syngeneic model of breast cancer, and significantly inhibited tumor expansion in a B16.F10 melanoma model. Notably, IMM20324 treatment resulted in the prevention of tumor growth following re-implantation of tumor cells, indicating the induction of immunological memory. Furthermore, exposure of IMM20324 correlated with decreased tumor volume and increased levels of intra-tumoral chemokines. Together, our data suggest that IL-38 is expressed in a high frequency of cancer patients and allows tumor cells to suppress anti-tumor immunity. Blockade of IL-38 activity using IMM20324 can re-activate immunostimulatory mechanisms in the tumor microenvironment leading to immune infiltration, the generation of tumor-specific memory and abrogation of tumor growth.